Response Towards Timang Xekory - Laura Pranti, Tutom; Yoesbar, Djaelani; Keezrawati, Mujan Yusuf (ERA, 2022)
Music is a form of entertainment that is enjoyed by people of all ages from every culture. It does not require any formal education to be understood or appreciated by the listeners. However, music is divided into several categories, and one of them is avant-garde music which can be fully appreciated through a specific approach because it contains elements, motifs, and beats that are inconsistent. It is also known for its complex and abstract music and has its own group of fans. A study of avant-garde music composition, Timang XekorY was conducted at Universiti Pendidikan Sultan Idris and Universiti Malaysia Sarawak. The respondents were categorised into two groups, the first was a group of musicians of music background and the second group is not of music background. Timang XekorY was inspired by the timang tuah ritual, which is commonly observed in Kapit, Sarawak. The research which was done against the backdrop of the rituals of the Iban community has yielded several findings. Firstly, a respondent said that a detailed explanation of the storyline of the ancient Iban singing text is needed. In addition, listeners or viewers who read of the programme book before the Timang XekorY show were found to have a better understanding of the storyline compared to those who have not been given the programme book or explanation of the original work.